2019
DOI: 10.18297/rgh/vol2/iss2/4
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible Dermatological Diseases Affecting Syrian Refugees in Lebanon

Abstract: The Syrian war led many to seek shelter in Lebanon, creating a major refugee crisis. Displaced populations in crowded unequipped settlements are vulnerable to infectious diseases. The burden and incidence of various transmissible skin conditions affecting Syrian refugees in Lebanon and their impact on the Lebanese public health system were evaluated. Literature regarding these conditions among Syrian refugees in host countries, and epidemiological data from the Lebanese Ministry of Public Health Surveillance U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Within the context of refugee crisis, the previous observational studies indicate that scabies is one of the most common diseases and the extent to which it may spread [19]. Rapid spread of scabies has been described in Lebanon with regards to migrant populations and asylum seekers, some of which include the time frame of the current Syrian crisis [20]. In a study conducted in Germany, scabies were detected in 16 of 52 patients, 40% of whom were Syrian asylum seekers [21].…”
Section: Discussionmentioning
confidence: 99%
“…Within the context of refugee crisis, the previous observational studies indicate that scabies is one of the most common diseases and the extent to which it may spread [19]. Rapid spread of scabies has been described in Lebanon with regards to migrant populations and asylum seekers, some of which include the time frame of the current Syrian crisis [20]. In a study conducted in Germany, scabies were detected in 16 of 52 patients, 40% of whom were Syrian asylum seekers [21].…”
Section: Discussionmentioning
confidence: 99%
“…This is out of the 4,837,134 Syrian refugees spread around the world. These refugees have been registered in Lebanon with the United Nations High Commissioner for Refugees (UNHCR) (Kawa, Hanna & Bizri 2019). Lebanon is collaborating with the UN and other international organizations to promote human-rights values at the personal and societal level (Kawa, Hanna & Bizri 2019;Burridge et al 2013).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…This fast response played a key role in the containment and has been recommended as an effective way for managing future outbreaks. 7 Hepatitis A Between 2010 and 2012, the annual average of reported hepatitis A cases in Lebanon was 509 (Figure 2). In 2014, a total of 2582 cases were reported, 33.3% of which were Syrian refugees.…”
Section: Mumpsmentioning
confidence: 99%
“…As per the Syrian Ministry of Health, tens of thousands of leishmaniasis cases are annually reported. 7 Available studies have shown that the Syrian crisis has increased the incidence of leishmaniasis in Syria, as well as in the neighboring countries. As per Sharara and Kanj, 5 the high concentration of Syrian refugees, poor sanitation, and bad living conditions together with limited health-care access in rural areas contributed to the higher burden of leishmaniasis in Lebanon.…”
Section: Mumpsmentioning
confidence: 99%